2009
DOI: 10.1007/s00439-009-0770-2
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association identified the common genetic variants influence disease severity in β0-thalassemia/hemoglobin E

Abstract: b-Thalassemia/HbE disease is clinically variable. In searching for genetic factors modifying the disease severity, patients were selected based on their disease severities, and a genome-wide association study (GWAS) was performed. Genotyping was conducted with the Illumina Human 610-Quad BeadChips array using DNAs from 618 Thai b0-thalassemia/HbE patients who were classified as 383 severe and 235 mild phenotypes by a validated scoring system. Twenty-three SNPs in three independent genes/regions were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
149
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(156 citation statements)
references
References 29 publications
6
149
1
Order By: Relevance
“…Clinical observations in rare b-thalassemia patients with elevated production of HbF showed that these increased levels resulted in a milder clinical course and infants with b-thalassemia only begin to show symptoms after the expression of HbF declines in the months following birth (Weatherall 2001;Weatherall and Clegg 2001). Larger epidemiological studies of thalassemia populations have confirmed such findings (Premawardhena et al 2005;Galanello et al 2009;Nuinoon et al 2010). While it has been difficult to tease apart the extent to which increased HbF production can ameliorate symptoms in thalassemia because it is difficult to ascertain the extent of g-globin production directly in patients with the need for frequent blood transfusions and such a great extent of ineffective erythropoiesis, a recent analysis in untransfused patients with b-thalassemia shows the quantitative ameliorating effect of HbF levels on clinical severity in this disease as well (Musallam et al 2011).…”
Section: The Fetal-to-adult Globin Switchmentioning
confidence: 79%
See 2 more Smart Citations
“…Clinical observations in rare b-thalassemia patients with elevated production of HbF showed that these increased levels resulted in a milder clinical course and infants with b-thalassemia only begin to show symptoms after the expression of HbF declines in the months following birth (Weatherall 2001;Weatherall and Clegg 2001). Larger epidemiological studies of thalassemia populations have confirmed such findings (Premawardhena et al 2005;Galanello et al 2009;Nuinoon et al 2010). While it has been difficult to tease apart the extent to which increased HbF production can ameliorate symptoms in thalassemia because it is difficult to ascertain the extent of g-globin production directly in patients with the need for frequent blood transfusions and such a great extent of ineffective erythropoiesis, a recent analysis in untransfused patients with b-thalassemia shows the quantitative ameliorating effect of HbF levels on clinical severity in this disease as well (Musallam et al 2011).…”
Section: The Fetal-to-adult Globin Switchmentioning
confidence: 79%
“…Understanding the mechanism of action by which these variants result in alterations in HbF levels is important, as the genetic variants at this locus appear to have as great or perhaps even a greater effect on clinical morbidity in the b-hemoglobinopathies as those variants at the BCL11A locus (Galanello et al 2009;Nuinoon et al 2010). Interestingly, this region contains a variety of regulatory elements that have been suggested to have an important role in regulating expression of MYB in erythroid progenitors (Mukai et al 2006;Wahlberg et al 2009;Stadhouders et al 2011).…”
Section: Switch From Fetal To Adult Hemoglobinmentioning
confidence: 99%
See 1 more Smart Citation
“…GWASs in Asian populations do not have the problem of sparse linkage disequilibrium like GWASs in African populations, and they have been successfully utilized to identify common variants with large effects in Thais. 16 Thus, the failure of the initial GWAS in Asian TB is not due to the problem of SNP coverage in the current microarray genotyping platform. Taking into consideration the caveats that might affect the power of a GWAS in identifying genetic risks to common diseases 17 and our experience of the increasing power of linkage analysis of TB by the subset-ordered analysis based on the age at onset of TB sibpairs, 10 we hypothesized that a gene-environmental effect (G X E) interaction, such as bacille calmette guerin (BCG) vaccination, exposure to different strains of M. tuberculosis, 18 or misclassification, might cause heterogeneity in TB.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have substantiated the quantitative ameliorating effect of increased fetal hemoglobin production on the clinical course in a variety of patients with NTDT. 76,[95][96][97][98][99][100] The earliest attempts to induce fetal hemoglobin through DNA methylation inhibition with 5-azacytidine were encouraging, although these were later hampered by concerns about the safety of this agent. 101 More recently, this approach has been revisited with the use of a safer demethylating agent, decitabine.…”
Section: Fetal Hemoglobin Inductionmentioning
confidence: 99%